Biological evaluation of solutions from bioglass, bioglass modified with cobalt, and calcium hydroxide - Amadeu, João Rafael [UNESP]; Silva, Isabela Joane Prado [UNESP]; Goto, Juliana [UNESP]; Reis-Prado, Alexandre Henrique Dos; Caiaffa, Karina Sampaio [UNESP]; Crovace, Murilo Camuri; Cintra, Luciano Tavares Angelo [UNESP]; Delbem, Alberto Carlos Botazzo [UNESP]; Duque, Cristiane [UNESP]; Benetti, Francine [UNESP] (FapUNIFESP (SciELO), 2025)
This study evaluated the cytotoxicity, biocompatibility, and bioactivity potential of bioglass solutions (F18 and F18 with cobalt; F18-Co) compared to Ca(OH)2 solution, to determine their suitability for use in vital pulp therapy. F18 bioglass was prepared, with a part being doped with cobalt. The solutions were prepared at a 1:10 powder-to-water ratio. L929 fibroblasts viability was assessed (MTT assay; 24 and 48-h). Tubes containing fibrin sponges embedded with either the solutions or saline (control) were prepared (16 tubes/group) and immediately implanted into 16 rats (4 tubes/rat). At 7 and 30 days, the euthanized rat specimens were analyzed for inflammation and bioactivity. The ANOVA with Tukey's test, or Kruskal-Wallis with Dunn's test was performed (p < 0.05). Undiluted, 1:2, and 1:4 diluted solutions reduced cell viability at 24-h (p < 0.05). The 1:8 and 1:16 dilutions of F18 and F18-Co exhibited cell viability similar to that of the control (p > 0.05), whereas Ca(OH)2 was cytotoxic (p < 0.05). At 48-h, F18 dilutions (undiluted, 1:2, and 1:4) exhibited similar results to the control (p > 0.05). F18-Co at 1:8 and 1:16 dilutions increased cell viability compared to Ca(OH)2 (p < 0.05) and were similar to the control (p > 0.05). On day 7, moderate-to-severe inflammation (p > 0.05) and thick fibrous capsule were observed. On day 30, mild inflammation was observed in the control and F18-Co groups, moderate inflammation in F18 (p < 0.05), and mild inflammation in Ca(OH)2 (p > 0.05). The fibrous capsule was thin. None of the materials exhibited positive structure in von Kossa and polarized light analysis. The F18 and F18-Co solutions are cyto- and biocompatible; however, no bioactivity was observed.